The Economics of Foreign Exchange and Global Finance - Wang, Peijei (Springer, 2012)
The book presents all major subjects in international monetary theory, foreign exchange markets, international financial management and investment analysis. It is relevant to real world problems in the sense that it provides guidance on how to solve policy issues as well as practical management tasks. This in turn helps the reader to gain an understanding of the theory and refines the framework. Various topics are interlinked so the book adopts a systematic treatment of integrated materials relating different theories under various circumstances and combining theory with practice. The text examines issues in international monetary policy and financial management in a practical way, focusing on the identification of the factors and players in foreign exchange markets and the international finance arena. The textbook can be used in graduate and advanced undergraduate programmes in these areas. The second edition incorporates two new chapters, integrating new materials, data, and recent developments.